Supercapacitor and magnetic properties of Fe doped SnS nanoparticles synthesized through solvothermal method. (25th August 2022) - Dar, Mohd Arif; Govindarajan, D.; Batoo, Khalid Mujasam; Siva, C.
Abstract: We report the synthesis of pure and Fe doped SnS nanoparticles through the solvothermal method. Fe with different contents (0, 2, 4, and 6 %) were doped in SnS and designated as N1, N2, N3 and N4, respectively. The samples were characterized using X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Raman, X-ray photoelectron spectroscopy (XPS), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Cyclic voltammetry (CV), Charging/discharging (GCD) and Vibrating sample magnetometer (VSM) analysis. XRD patterns confirm that N 1, N2, N3, and N4 samples form an orthorhombic crystal structure. Based on the FT-IR and Raman results, a minor stretching vibration in Sn-S modes was observed in pure SnS and Fe doped SnS samples. SEM study shows samples exhibit ball-like spherical shapes, while the average particle size calculated from TEM images shows sizes between 25 and 30 nm. XPS confirm the chemical composition and binding energy of pure and Fe-doped SnS. Specific capacitance values for pure N1 electrode 419 F/g increases to 1242 F/g with Fe (%) doping which shows that doping has enhanced the electrochemical performance of SnS nanoparticles. The optimized assembled supercapacitor shows a high energy density of 34 Wh kg −1 at a power density of 3214 W kg −1 and owed 98.5 % columbic efficiency with 94.2 % capacitance retention after 5000 cycles. Room temperature Hysteresis measurement show samples exhibit weak ferromagnetism and the saturation magnetization increases with Fe doping. Magnetic studies suggest samples have the potential for data storage applications. Highlights: A solvothermal method is applied for the synthesis of pure and Fe doped SnS nanoparticles. Electrochemical performance of pure and Fe doped SnS electrodes determine that they are technically and economically effective. The sustainability of these electrodes is superior to other conventional electrodes.